Aperiodic nanoplasmonic devices for directional colour filtering and sensing - Matthew S. Davis (Nature Portfolio, 2017)
Devices based on periodic architectures are intrinsically limited in terms of spectral response. Using an interference-based model, the authors design and fabricate plasmonic aperiodic groove array devices which function as light filters and colour sorters with flexible, multi-spectral optical response.